Strategi Glocalization UMKM Industri Kreatif Lokal dalam Menghadapi Dinamika Ekonomi Digital: Studi Kasus Thasya Ethnic Bandar Lampung - Annisa Nisfisyahrini Halim; Ghina Roudhotul Jannah; Sultan Naufal Muzakki; Pijar Syiffa Aditama; Ihsan Fadillah Putra; Muhammad Surya Santoso (Sinesia : Jurnal Pengabdian Masyarakat, 2026)
Globalization, marked by the influx of foreign product trends and lifestyles, has shifted public consumption preferences, including in Lampung, causing local culture-based creative industry products to become increasingly marginalized in the domestic market. This condition has been exacerbated by global geopolitical uncertainty, which has triggered operational policy changes such as Work From Home (WFH), fundamentally transforming consumption patterns into digitally driven behaviors. These dynamics pose a serious challenge for local creative industry MSMEs, which must compete amid increasingly complex economic pressures. This study aims to analyze the adaptation strategies of Thasya Ethnic MSME in Bandar Lampung in responding to changes in consumer behavior and economic instability. Using a qualitative descriptive method through direct observation and interviews, the study found that Thasya Ethnic implemented product innovation by transforming *tapis* fabric into functional products such as home décor and modern fashion items. In addition, the company applied operational efficiency through a home-based production system and output-based wage mechanisms to maintain stable cash flow. However, a crucial challenge identified was the inconsistency of digital promotion, which limited broader market reach. This study concludes that the integration of local cultural product innovation and sustainable digital marketing optimization is the key for creative MSMEs to survive through a Glocalization strategy, an approach that adapts local values to remain relevant and competitive within the global market landscape.